Cardiac Surgery Development in Cameroon: Unexpected Challenges From a Socio-Political Crisis - Mve Mvondo, Charles; Giamberti, Alessandro; Ngowe Ngowe, Marcelin; Mbuoh, Helen Anshoma; Milocco, Italo; Tsague Kengni, Hermann Nestor; Cirri, Silvia; Frigiola, Alessandro (Frontiers in Cardiovascular Medicine, 2022)
Despite the alarming and growing burden of cardiovascular diseases in the sub-Saharan Africa (SSA), there is still a huge lack of specialized institutions in the region with a mean of one cardio-surgical unit for 33 million inhabitants. Despite the numerous efforts from humanitarian organizations made in recent years, the setting up of cardio-surgical units in the region remains challenging with regards to long-term sustainability. Indeed, beside the lack of financial resources, the insufficient local expertise in addition to the inadequate health infrastructure, unpredictable threats from external factors such as recurrent conflicts and humanitarian crisis are still major concerns in an environment characterized by endemic socio-political instability. In Cameroon, located in the North West Anglophone region at 500 km from the capital, the cardiac centre of Shisong (CCS) is currently the lone cardio-surgical institution of the country. Fruit of a joint initiative of two Italian Non-governmental organizations namely, Bambini Cardiopatici nel Mondo (ABCnM) and Cuore Fratello (CF), and a local religious partner, the Tertiary Sisters of Saint Francis (TSSF), the CCS was faced with in the middle of a socio-political crisis that led to urgent need of revision of the cardio-surgical project. The current paper reviews the impact of the ongoing socio-political crisis on the CCS over the past three years, in terms of clinical activities, staff perspectives and long-term sustainability.